Analysis of environmental care attitudes based on students’ ecological intelligence - El Rizaq, Agung Dwi Bahtiar; Utami, Wiwik Sri; Abdullah, A. Fatikhul Amin; Romadhon, Sahrul; Ibrahim, Mohd Hairy (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Ecological intelligence is crucial in enhancing human awareness of environmental issues. However, there is a lack of research on how environmental care attitudes are developed through the learning process in the classroom. This study aims to explore how students perceive environmental care attitudes based on ecological intelligence. The research used a quantitative methodology with a percentage technique and involved 120 students from Madrasah as the sample. Research data were obtained through a closed-ended questionnaire, and the data were analyzed through percentages. The findings show that students possess a high level of environmental care, as evidenced by the highest agreement level in the head (cognition) or learning to know with 89.3%, followed by the heart (affection) or learning to be with 86.5%, and then the hands (conation) or learning to do with 85.6%. The result indicates that students who participate in environmental care activities in school have good ecological intelligence. These results suggest that integrating ecological intelligence into classroom learning can effectively foster environmental care attitudes. Therefore, educators and curriculum developers should consider incorporating more environmental education components into daily instruction. Future research may explore the long-term impact of ecological intelligence-based learning on students’ environmental behavior outside school.